PERANCANGAN USER INTERFACE DAN USER EXPERIENCE APLIKASI BERBASIS WEB UNTUK KLINIK TERAPI MENGGUNAKAN METODE USER CENTERED DESIGN (STUDI KASUS: KLINIK RUMAH TERAPI SAHABAT) - Rachim, Fauziyah Aulia; Irmawati, Budi; Afwani, Royana (Program Studi Teknik Informatika, Fakultas Teknik, Universitas Mataram, 2024)
Rumah Terapi Sahabat Clinic is located in West Pagesangan, West Nusa Tenggara and has been around for seven years since it was founded in 2015. Based on the results of observations, Focus Group Discussions and interviews, this clinic needs a way to digitize clinical data storage so that it can be accessed easily by clinic staff. In order to meet these needs, a website-based application for clinics is needed with patient and therapist data storage features as well as therapy scheduling. To be able to realize this application, User Interface and User Experience are needed. The method used to do this is User Centered Design. After creating a good User Interface, testing will be carried out using the System Usability Scale and User Experience Questionnaire methods to find out how functional and experienced the clinical staff are while using this Front-end prototype and aspects that can be improved in the future. This research will have results in the form of a front end of a website-based application that suits the needs of clinic staff. While testing using SUS and UEQ, the end result of SUS is 84 or “Acceptable” meanwhile five out of six categories from UEQ are graded “Excellent”